Influence of environmental quality of the tributaries of the Monjolinho River on the relative condition factor (Kn) of the local ichthyofauna - Barrilli, Germano Henrique Costa; Rocha, Odete; Negreiros, Natalia Felix; Verani, José Roberto (Biota Neotropica, 2015)
The relative condition factors (Kn) of the fishes Astyanax paranae, Phalloceros harpagos and Poecilia reticulata were used as a means of assessing the influence of environmental conditions on the well-being of sub - populations of these species, with the eventual aim of using them as bioindicators of disturbance in tributary streams of the Monjolinho River, in São Carlos - SP. The power-law curve generated by the length-weight relationship indicated a positive allometric growth for the three species studied. Overall, the canonical correspondence analysis (CCA) positively correlated average Kn of A. paranae with well oxygenated and oligotrophic environments, typical of conserved areas or near the natural state. For the average value of Kn obtained for Phalloceros harpagosspecies, there was no significant difference between natural and disturbed areas. However, the CCA positively correlated the mean Kn of the speciesP. reticulata from similar environments with higher trophic level, suggesting that this species is indicative of disturbance.